1995
DOI: 10.1007/bf00042066
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression of rpoC2 in CMS and fertile lines of sorghum

Abstract: A 165 bp deletion in the middle of rpoC2, the plastid gene which encodes the RNA polymerase beta" subunit, was identified in the small-anthered types of CMS sorghum, Sorghum bicolor (L.). Moench, containing A1, A2, A5, and A6 cytoplasms. It was previously shown that the amino acid sequence deleted in these CMS lines is in a monocot-specific region that contains several protein motifs that are characteristic of several transcription factors. Using primers flanking the deletion in PCR analyses, various types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Analysing cytoplasmic male sterile (CMS) lines of Sorghum , Chen et al 37 discovered a 165 bp deletion in this insertion region that suggests a possible relation between this deletion in rpoC2 and the CMS-system. 38 So far this deletion was only observed in Sorghum but sequence comparisons (data not shown) revealed that one deletion that results in the shorter L. perenne rpoC2 gene is located in the same region where the deletion occurs in Sorghum . Hence a higher susceptibility to variation in this gene region could be indicated and an investigation of L. perenne CMS lines in regard to variation to fertile lines may prove valuable for improving future Lolium breeding schemes.…”
Section: Resultsmentioning
confidence: 93%
“…Analysing cytoplasmic male sterile (CMS) lines of Sorghum , Chen et al 37 discovered a 165 bp deletion in this insertion region that suggests a possible relation between this deletion in rpoC2 and the CMS-system. 38 So far this deletion was only observed in Sorghum but sequence comparisons (data not shown) revealed that one deletion that results in the shorter L. perenne rpoC2 gene is located in the same region where the deletion occurs in Sorghum . Hence a higher susceptibility to variation in this gene region could be indicated and an investigation of L. perenne CMS lines in regard to variation to fertile lines may prove valuable for improving future Lolium breeding schemes.…”
Section: Resultsmentioning
confidence: 93%
“…Among the nine positively selected genes, rpoC2 encodes the RNA polymerase β”. A comparison of rpoC2 between fertile lines of sorghum and cytoplasmic male sterile lines showed that a 165 bp deletion was identified that encodes several protein motifs involved with transcription factors; this region might play an important role in the regulation of developmental pollination [89]. The Siraitia species are dioecious, so the finding that rpoC2 evolved under positive selection might indicate that it is essential for sex differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Of the genes coded by at least 85 of the genomes we found the lowest rejection rates for psbN (1 of 97 genomes) a gene of unknown function associated with the biogenesis of both photosystems [ 35 ], rpoC2 (2 of 97 genomes) a component of the plastid RNA polymerase [ 36 ], ycf4 (2 of 93 genomes), which codes a non-essential assembly factor of photosystem I [ 37 ], rpl20 and rpl36 (3 of 98 each), both encoding ribosomal proteins, rpoA (3 of 95) and rpoC1 (3 of 91), both of which encode plastid RNA polymerase components [ 38 ], ccsA (3 of 86), which appears to encode a protein involved in heme attachment to chloroplast cytochromes [ 39 ], rpl23 (4 of 95), encoding a ribosomal protein and ycf3 (4 of 87), whose function is unknown but may be related to photosystem biogenesis [ 37 ].…”
Section: Resultsmentioning
confidence: 99%